PENGEMBANGAN MEDIA POP UP BERTEMA BANJIR SEBAGAI UPAYA MENINGKATKAN KOSA KATA ANAK TK B - Hidayati, Agustin Dwi Nur; Prasetyo, Agung; Khasanah, Ismatul (Universitas Muhammadiyah Ponorogo, 2025)
This research is motivated by the problem of children's speaking ability. Children tend to be less able to express what is in their minds, convey ideas, it is because they do not have too much vocabulary. This type of research is development or Research and Development (RnD). The development procedure in this study applies the ADDIE model procedure (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were kindergarten B class teachers from several kindergartens in Jaken District. The collection technique used a questionnaire. The data were obtained from questionnaires of media experts, materials and teacher responses. The results of the analysis on media experts were 83% with a very feasible category, material experts were 80% with a feasible category, and questionnaire responses from teachers were 83% with a very feasible category. This shows that Pop Up Flood media can make it easier for children to understand flooding and improve children's learning outcomes and can be used as media in kindergarten B class. Based on the results of this study, Pop Up Flood media can be used by teachers as an alternative media in the classroom to support children's learning activities.